2011
DOI: 10.1016/j.ejcts.2011.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Even short-time storage in physiological saline solution impairs endothelial vascular function of saphenous vein grafts

Abstract: Even short-time storage in PSS significantly impairs endothelial vascular function. Concerning the essential role of a faultless endothelial layer, the quite common use of PSS as a storage solution for SVSs in CABG surgery has to be discussed critically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 15 publications
1
66
0
6
Order By: Relevance
“…19, 20 GALA, as the most widely recognized of these solutions, was used for physiologic characterization along with more traditional solutions. GALA contains glutathione and L-ascorbic acid, antioxidants, and arginine, a substrate for nitric oxide synthase in endothelial cells, which were added to a buffered electrolyte solution.…”
Section: Discussionmentioning
confidence: 99%
“…19, 20 GALA, as the most widely recognized of these solutions, was used for physiologic characterization along with more traditional solutions. GALA contains glutathione and L-ascorbic acid, antioxidants, and arginine, a substrate for nitric oxide synthase in endothelial cells, which were added to a buffered electrolyte solution.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the regular course of bypass graft surgery, vein and artery grafts are stored at room temperature for Ͻ2 hours. 4 However, it could be reasonable to keep vessel segments of patients with a desperate graft situation for later reimplantation should early graft failure occur. Here, cold storage is advised.…”
mentioning
confidence: 99%
“…Although the mechanisms of VGF are not completely understood, endothelial damage during vein graft harvesting and implantation is known to be an important cause of acute and intermediate VGF. 8,9 Although significant attention has been given to various harvesting techniques to minimize trauma, 10 intraoperative graft preservation solutions have not been investigated in recent clinical studies. The lack of evidence is illustrated by a lack of consensus and variation in the use of vein graft preservation solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gundry et al 12 showed that storage in a saline solution had deleterious effects on endothelial function compared with preservation in autologous blood, other studies 13-18 aiming to substantiate these findings have shown conflicting results. Other studies 9,15,16,19-23 have investigated the effect of storage in various buffered saline solutions on vessel wall tension and endothelial function in discarded vein graft segments and overall have shown improved endothelial function after preservation in a buffered saline storage solution compared with saline- and/or blood-based media.…”
Section: Discussionmentioning
confidence: 99%